ARRANGEMENT OF BANKRUPTCY DEBT REPAYMENT TOWARD EMPLOYEES IN INDONESIA AND GERMANY - Putri Ariqah; Siti Anisah (Indonesia Private Law Review, 2022)
Employees have special rights in the settlement of bankrupt debts to obtain their rights as regulated in the Indonesian Bankruptcy Law. However, employees must compete with other creditors who also have privileges under bankruptcy law, such as the tax office, insurance policy holder, and bankruptcy fees. Due to the existence of several special creditors, employees do not get their rights in the first order as regulated in the labor law. This study aims to determine the mechanism for filing bankruptcy against debtors in terms of legal entities and the position of employees in paying bankruptcy debts compared to other creditors in the Indonesian and German legal systems. This type of research is normative legal research conducted by examining library materials or secondary data. This study analyzes the mechanism for filing bankruptcy against debtors as legal entities according to the Indonesian and German legal systems which are divided into 3 (three) stages, namely registration, trial, and implementation of the bankruptcy decision. The position of employees in the settlement of bankrupt debts differs between Indonesia and Germany. In Indonesia, for the payment of ''wages'', the position of employees has a ''privilege'' which takes precedence over other creditors. However, for the settlement of ''other rights'' owned by employees, they do not have a privileged position as wages, so they are not included in priority payments. Whereas in Germany, there is a special feature called “bankruptcy money” where the payment of three months' wages will be paid at the preliminary stage of the bankruptcy proceedings. In addition, the position of rights to the social plan, the position of employee receivables are payments that are prioritized over other creditors. Finally, rights that are not included in the bankruptcy money, whose position in a settlement is after the demands of the creditor whose position is higher than the unsecured creditor have been fully fulfilled.